Batasan Asas Kebebasan Berkontrak Dalam Kredit Pemilikan Rumah - Sri Wirda Ningsih (Officium Notarium, 2022)
Home is the need of every human being. However, not everyone can buy a house, considering houses have economic value, which means that the longer they are, the more expensive they are. The solution to this is that there are banking financial institutions that provide credit facilities in the form of Home Ownership Loans (KPR). Agreements in mortgages often place customers and banks in an unequal position, so that the existence of the principle of freedom of contract in housing loans (KPR) is debated. Based on this, it is necessary to conduct further research regarding the limitations of the principle of freedom of contract in housing loans (KPR). Therefore, the researcher formulates a problem formulation regarding how are the limitations of the principle of freedom of contract in housing loans (KPR)? The research method used is normative with library research. The results of the study conclude that in housing loans (KPR), the principle of freedom of contract is not absolute and can be interpreted as freedom as freely as possible. The principle of freedom of contract has limitations regulated in laws and regulations. Regarding Home Ownership Loans (KPR), it still provides a choice of agreement between the parties. If the customer agrees, then they can take it but if they do not agree, the agreement is not necessarily binding on both parties. Therefore, KPR still pays attention to the existence of an agreement between the parties.Key Word: Agreement, Freedom of Contract Principle, Home Ownership Loan AbstrakRumah adalah kebutuhan setiap manusia. Membeli rumah tidak semua orang dapat melakukannya, karena rumah mempunyai nilai ekonomis yang berarti bahwa semakin lama akan semakin mahal. Solusi atas hal tersebut, terdapat lembaga keuangan perbankan yang menyediakan fasilitas kredit dalam bentuk Kredit Pemilikan Rumah (KPR). Perjanjian dalam KPR seringkali menempatkan nasabah dengan bank pada posisi yang tidak seimbang, sehingga keberadaan asas kebebasan berkontrak dalam Kredit Kepemilikan Rumah (KPR) diperdebatkan. Berdasarkan hal tersebut, perlu dilakukan penelitian lebih lanjut mengenai batasan asas kebebasan berkontrak dalam Kredit Pemilikan Rumah (KPR). Oleh karena itu, peneliti merumuskan suatu rumusan masalah mengenai Bagaimanakah batasan asas kebebasan berkontrak dalam Kredit Pemilikan Rumah (KPR). Metode penelitian yang digunakan adalah normatif dengan studi kepustakaan. Hasil penelitian memberikan kesimpulan bahwa dalam Kredit Pemilikan Rumah (KPR), asas kebebasan berkontrak tidak mutlak dapat diartikan sebagai kebebasan yang sebebas-bebasnya. Asas kebebasan berkontrak mempunyai batasan-batasan yang diatur dalam peraturan perundang-undangan. Mengenai Kredit Pemilikan Rumah (KPR), tetap memberikan pilihan kesepakatan diantara para pihak. Jika nasabah setuju, maka ambillah dan jika tidak setuju maka perjanjian juga tidak serta merta mengikat kedua belah pihak. Oleh karena itu, KPR tetap memperhatikan adanya kesepakatan diantara para pihak.Kata-kata Kunci: Perjanjian, Asas Kebebasan Berkontrak, Kredit Pemilikan Rumah